9.0k views
9 votes
4x^2-2x-4=0 solve using quadratic formula

1 Answer

4 votes

Answer:

Explanation:

Although you can start with 4x^2-2x-4=0, it's just slightly easier to reduce the coefficients. 4x^2-2x-4=0 becomes 2x^2 - x - 2 = 0.

The discriminant (part of the quadratic formula) is b^2 - 4ac. Using b = -1. a = 1 and c = -2, we get (-1)^2 - 4(2)(-2), or 17.

-b ± √(b^2 - 4ac)

Then the quadratic formula x = ---------------------------

2a

-(-1) ± √17 1 ± √17

takes on the values x = ----------------- = ---------------

4 4

User Chic
by
5.5k points